Liver metastases 2 years after resection of a very-low-risk duodenal gastrointestinal stromal tumor: a case report - Junya Mita; Kazuhiro Tada; Yusuke Kuboyama; Shoji Hiroshige; Shun Nakamura; Junichi Takahashi; Kazuhito Sakata; Hiroshi Mizuuchi; Taro Oba; Fumitaka Yoshizumi; Kentaro Iwaki; Hideya Takeuchi; et al. (Surgical Case Reports)
Abstract Background Gastrointestinal stromal tumors (GISTs) are rare mesenchymal tumors, but are the most common mesenchymal tumors of the gastrointestinal tract. The risk classification of GISTs is based on the tumor size, mitotic index, tumor site, and presence of tumor rupture. Recurrence in the very-low-risk group is extremely rare. We herein report a case of liver metastases 2 years after resection of a very-low-risk duodenal GIST. Case presentation A 57-year-old woman presented to the hospital for evaluation of melena. Esophagogastroduodenoscopy showed bleeding from the exposed blood vessels at the top of a submucosal tumor approximately 20 mm in size located in the second (descending) part of the duodenum, and the bleeding was controlled with electrocoagulation. A GIST was suspected, and the patient underwent wedge resection of the duodenum. The resected specimen contained a 16- × 12-mm (< 20-mm) white submucosal tumor composed of spindle cells with a mitotic count of 4 per 50 high-power fields, and a histologically negative margin was achieved. Immunochemical analysis revealed positive tumor staining for c-kit protein and alpha-smooth muscle actin and negative staining for CD34, desmin, and S-100 protein. Therefore, the tumor was diagnosed as a very-low-risk duodenal GIST based on the Fletcher classification and modified Fletcher classification (Joensuu classification). The postoperative course was uneventful, and the patient was discharged on postoperative day 11. At the follow-up visit 2 years postoperatively, contrast-enhanced computed tomography revealed liver tumors in S8 and S6 measuring 26 × 24 and 10 × 10 mm, respectively. Both lesions showed peripheral dominant hyperenhancement with hypoenhancement inside, indicating tissue degeneration within the tumors. These imaging findings closely resembled those of the duodenal GIST. Hence, the patient was diagnosed with liver metastases of GIST 2 years postoperatively. She was subsequently started on treatment with 400 mg of imatinib. At the time of this writing (2 months after diagnosis), the patient was clinically well and asymptomatic and was continuing imatinib therapy. Conclusions Recurrence of very-low-risk GISTs is extremely rare. Even a small GIST with low mitotic activity can never be considered completely benign, and long-term follow-up is necessary.